IMPAC OF VOLATILITY EXCHANGE RATES ON INDONESIAN ELECTRONIC IMPORTS FROM INTRA AND EXTRA ASEAN - Muklis, Imam (Economic Journal of Emerging Markets, 2011)
This study analyzes the effects of exchange rates volatility and Gross Domestic Product (GDP) on electronic commodity import demand in Indonesia from intra and extra ASEAN. It applies an Error Correction Model along with Dickey-Fuller and Augmented Dickey-Fuller tests. It finds that Indonesian import demand for electronic commodity is significantly affected by GDP only in the short run. It also finds that exchange rates volatility in the short run have a negative effect on import demand from intra ASEAN and have a positive effect from extra ASEAN. In the long term, Indonesian import demand from extra ASEAN is positively affected only by exchange rates volatility. Keywords: Exchange rates volatility, error correction model, gross domestic product, ASEAN JEL classification numbers: F14, F31